Interfacial defect passivation by using diethyl phosphate salts for high-efficiency and stable perovskite solar cells. Issue 12 (7th March 2023) - Sha, Xuan; Sheng, Jiang; Yang, Weichuang; Sun, Jingsong; Shou, Chunhui; Zhang, Luyan; Zhang, Ningjun; Ying, Zhiqin; Yang, Xi; Zhao, Hongbin; Ye, Jichun
Abstract : 1-Ethyl-3-methylimidazolium diethyl phosphate (EMIM DEP) is used to passivate interface defects of SnO2 /perovskite and enhance the interface quality. The EMIM DEP-based device shows higher efficiency and stability, compared to pristine SnO2 . Abstract : The defects at the interface of the SnO2 electron transport layer (ETL) and the perovskite absorber, as the charge-carrier recombination centers, play an important role in determining the performance of perovskite solar cells (PSCs). Here, we use an organic salt, i.e., 1-ethyl-3-methylimidazolium diethyl phosphate (EMIM DEP), to passivate such defects, which could simultaneously enhance the interface quality and perovskite crystallization. The DEP groups saturate the dangling bonds of surface Sn atoms, efficiently suppressing the interfacial charge recombination and tailoring the energy alignment of the SnO2 /perovskite interface for better carrier extraction. Additionally, EMIM DEP not only improves the crystal growth of perovskite, but also passivates the defects of the perovskite grain boundary. Consequently, the EMIM DEP-based device presents a champion power conversion efficiency (PCE) of 23.21%, which is much higher than that of the control device (21.14%). The EMIM DEP-based device retains 95% and 87% of its original PCE after storage for over 2000 h in a 30 ± 5% RH ambient air and under operation at the maximum power point for 700 h, respectively. Therefore, it is demonstrated that interface modification via such an organic salt is a feasible and efficient approach to improve the passivation and contact properties for high-efficiency and stable PSCs.